Legalitas Hukum Internasional Tentang Pengakuan Negara–Negara Terhadap Konflik China Dan Taiwan - Felix Brayen Uruilal; Josina Augustina Yvonne Wattimena; Lucia Charlota Octovina Tahamata (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The state sovereignty dispute between China and Taiwan Hostility also occurs between the authorities of China and Taiwan, which are the 23rd province of China but are administratively separated, which talks about the legality of international legal recognition.Purposes of the Research: This study aims to examine the status of Taiwan in the sovereignty of the State of China, as well as the legality of international law on the recognition of countries in the conflict between China and Taiwan.Methods of the Research: This research is a normative juridical research by means of research conducted by collecting primary, secondary, tertiary data obtained by using a literature study. The data that has been collected is analyzed qualitatively, the descriptions of which are arranged systematically based on discipline, legal science to achieve clarity on the issues to be discussed.Results of the Research: The status of Taiwan in the sovereignty of the State of China is the status quo where Taiwan does not have international sovereignty, is not de facto independent, Taiwan is a country because it already has a clear population, territory, area and government. However, de jure Taiwan has not yet been recognized as a country by the international community and the United Nations. The legality of international law in the case of China and Taiwan is a collection of laws which mostly consist of principles and rules that must be obeyed by countries. for that there must be a permanent recognition to be one of the concepts that determine the criteria of a state in international law which is contained in three opposing theories, namely Constitutive Theory, Declarative Theory, and Middle Way Theory. In this theory clearly get the legality of the problems that occur between China and Taiwan.